MEKANISME TRANSAKSI JUAL BELI PRODUK MINUMAN DENGAN MENGGUNAKAN VENDING MACHINE DALAM PERSPEKTIF FIQH MUAMALAH - Denden S Hadi Wijaya (Mutawasith: Jurnal Hukum Islam, 2018)
The development of increasingly rapid technology, the world of trade also has its own style, to things that are practical. Technical trading no longer says consent and qabul, but is accustomed to the internet system. This study aims to determine the law of buying and selling beverage products using vending manchine muamalah fiqh perspective. The method used is library research. Types of qualitative descriptive approaches. The research data is divided into primary data and secondary data relating to muamalah fiqh. From the study concluded: 1) The mechanism of buying and selling transactions using vending machines is almost the same as how to operate using an ATM machine, the owner of the machine has included the mechanism of buying and selling drinks using an automatic machine that has a price, or the machine cannot return the remaining money, consumers agree to a decision that has been taken by the manufacturer. 2) The mechanism of buying and selling transactions according to muamalah perspective there are several pillars of buying and selling: people who have the intention, sighat, goods purchased and the exchange rate, if the four pillars are not fulfilled then the sale and purchase is invalid. 3) Legal analysis of the sale and purchase of beverage products using a vending machine perspective muamalah fiqh, scholars namely Hanafiyah, Malikiyah, and Hambali allow. Whereas according to the Shafi'i school of thought it is not valid except with the consent and qabul